Inovasi Politik : Kiprah Legislator PKS di Parlemen Kota Pangkalpinang Periode 2019-2024 - Dimas Ali Sopin; Ranto Ranto (Jurnal Studi Inovasi, 2023)
Gait in parliament is an important part that does not escape from the sight of political parties’s eyes. Cadres as representation from political parties occupying seats in parliament are expected to be able in taking part of realizing people’s aspirations, so the administration of regional government becomes more dynamic. The aim of this research were: 1) Analyzing the progress of PKS legislators in Pangkalpinang City’s parliament; and, 2) Analyzing the influencing factors of progress from PKS legislator in Pangkalpinang City’s parliament. This research was conducted at Prosperous Justice Party (PJP) Parliament, Pangkalpinang City in 2022 using qualitative method through descriptive approach. This research used primary data and secondary data from the chairperson, management, and cadres of Prosperous Justice Party collected through observation, interview, and documentation. The result of this research showed that: 1) Prosperous Justice Party optimizing legislator’s work through the faction in DPRD of Pangkalpinang City by strengthening the function in parliament through quantity and quality increasing of cadres in government as evidenced by the increase in seat acquisition from 2 seats in 2014 until 2019 to 3 seats in 2019 until 2024; and, 2) Prosperous Justice Party employs various strategies to realizing aspirations, which are influential factors in gait, including the process of conveying convincing details of aspirations at plenary meetings, negotiating several parties using reciprocal relationships, and periodic internal evaluation. However, the realization of this aspirations faces several obstacle, including budget constraints, and political interest with certain people. Keywords: Government, Legislator’s Work, Parliament, and Factor.